Sentiment Analysis Related to Law No. 6 Of 2023 on the Employment Cluster Using the Bidirectional Long Short-Term Memory Algorithm - Anugra M; Munawar (Penerbit Jurnal Indonesia, 2024)
The enactment of UU Cipta Kerja has triggered varied public responses, particularly concerning employment provisions like fixed-term employment (PKWT), the legalization of outsourcing, unfair severance pay, and ease of layoffs. Social media has become a primary platform for the public to share opinions on issues within the law’s employment cluster. This study employs sentiment analysis using the Bidirectional Long Short-Term Memory (Bi-LSTM) algorithm to understand public sentiment about UU Cipta Kerja and sentiment within its content. Bi-LSTM is chosen for its ability to capture temporal relationships and context in long texts, which aids in handling complex sentiment classification. The findings indicate varied public perceptions: neutral sentiment dominates issues like